ANALISIS PELAYANAN PERIZINAN PADA KANTOR BADAN PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (BPM-PTSP) KABUPATEN POLEWALI MANDAR - Rustan IR. (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2016)
ABSTRACKThis paper aims to find out, understand, and analyze the success and quality of one-stop integrated licensing services, and the Implementation of One-Stop Integrated Licensing Services. The method used is a qualitative descriptive approach. Primary data is obtained from interviews and observations, while secondary data is obtained from documentation studies. Data analysis using triangulation method. The results showed that the commitment to implement BPM-PTSP in Polewali Mandar District from the regional head was good, but the constraints were found in terms of the coordination function between PTSP implementing institutions and technical SKPD due to differences in echelonization. The impact of attraction between the two institutions in licensing public services can have an impact on the low trust of business people in public service providers. The one-stop integrated licensing service, which is held by Polewali Mandar Regency KPTSP has not been successful and has not yet been qualified. This can be seen from the non-fulfillment of the degree of conformity required between the three dimensions of conformity proposed by Korten, namely policies/programs, users and implementing organizations. This also shows that Korten's suitability theory has no relevance to the reality of the implementation of one-stop integrated licensing services in Polewali Mandar Regency.